Comparison of EMC and durability of heat treated wood from high versus low water vapour pressure reactor systems. (February 2015) - Willems, W.; Altgen, M.; Militz, H.
<x content-type="archive" xml:space="preserve">Abstract</x> A large number of different heating technologies has been put into use for industrial scale thermal modification of wood. A useful classification of these processes is by the level of water vapour pressure, which ranges from vacuum to high saturated steam pressures. Only high water vapour pressure systems can maintain a finite moisture content during the heat treatment, but little is known about the water vapour pressure dependence of the thermal modification chemistry and the resulting modified wood properties. It is concluded from our analysis that the thermal wood reaction chemistry at the molecular functional group level is quite independent of the process and wood species. Wood properties that are strongly determined by wood chemical composition, such as the fungal durability and the equilibrium moisture content (EMC), can hence be equally achieved by all processes and for all wood species. This finding cannot be transferred to every other thermally modified wood property.